FIGURATIVE LANGUAGE AND HUMOR ANALYSIS IN CHRISTIAN GIACOBBE’S INDONESIAN STAND-UP COMEDY PERFORMANCES - Muhammad Alhafiz Dinanda; Deliana Deliana; Rahmadsyah Rangkuti (Linguists : Journal of Linguistics and Language Teaching, 2026)
This study investigates the use of figurative language and its influence on joke structure in the stand-up comedy of Christian Giacobbe, an Italian performer active in the Indonesian comedy scene. Despite growing research on humor and figurative language, few studies have examined how figurative language systematically functions within the setup–punchline structure in cross-cultural stand-up comedy. Adopting a qualitative descriptive approach, the research analyzes 41 jokes across 14 performances selected from YouTube, focusing on how figurative language contributes to comedic rhythm, cultural framing, and audience engagement. The analysis applies Kennedy’s (1995) typology of figurative language and Attardo’s (1994) general verbal theory of humor (GVTH) to examine how various figurative language are strategically placed within the setup–punchline structure. Findings reveal that contradictive figurative language dominates the punchlines, delivering surprise and critique, while comparative forms appear in setups to build contextual contrast. Symbolic references further enrich the cultural depth and communicative resonance of the humor. The study concludes that figurative language not only enhances joke construction but also serves as a powerful tool for cross-cultural connection and commentary, particularly in multilingual and multicultural settings like Indonesia. This study contributes by demonstrating that figurative language as a structural mechanism in humor construction, rather than merely as a stylistic feature, particularly through its alignment with GVTH components.